Copper Tolerance Mechanism of the Novel Marine Multi-Stress Tolerant Yeast Meyerozyma guilliermondii GXDK6 as Revealed by Integrated Omics Analysis - Bu, Ru; Yan, Bing; Sun, Huijie; Zhou, Mengcheng; Bai, Huashan; Cai, Xinghua; Mo, Xueyan; Su, Guijiao; Jiang, Chengjian (Frontiers in Microbiology, 2021)
Various agricultural products used in food fermentation are polluted by heavy metals especially copper, which seriously endanger human health. Methods to remove copper with microbial strategies have gained interests. A novel Meyerozyma guilliermondii GXDK6 could survive independently under high stress of copper (1400 ppm). The copper tolerance mechanism of GXDK6 was revealed by integrated omics in this work. Whole-genome analysis showed that nine genes (i.e., CCC2, CTR3, FRE2, GGT GST, CAT, SOD2, PXMP4, and HSP82) were related to GXDK6 copper tolerance. The expression of glutathione metabolism related genes, GSH content and GST activity were elevated by copper stress, suggesting enhanced copper conjugation and detoxification in cells. The inhibited copper uptake by Ctr3 and enhanced copper efflux by Ccc2 contributed to the decrease in the intracellular copper concentration. The improved expression of antioxidant enzyme genes (PXMP4, SOD2, and CAT), accompanied by the enhanced activities of antioxidant enzymes (POD, SOD, and CAT) resulted in a decrease in copper-induced ROS production, protein carbonylation, lipid peroxidation and cell death. The metabolite D-mannose against harsh stress conditions beneficial to improving copper tolerance. This study contributed to understanding the copper tolerance mechanism of M. guilliermondii and its application in removing copper during fermentation.